Narrative research in applied linguistics - Barkhuizen, Gary Patrick (New York : Cambridge University Press, 2013)
'This book brings together contributions from various researchers, providing an overview of narrative research approaches and demonstrating how these work in practice. A broad range of approaches are covered, from well-established and well-known thematic analysis (particularly of'big stories'), to the more recent sociolinguistic discourse analysis of'small stories', and the innovative analysis and presentation of visual and performance data such as drawings and drama. This overview includes not just an illustration of narrative research, but the methodological processes which underpin it, relating these to relevant narrative theory. The book, therefore, is both a how-to-do narrative research text and a presentation of narrative studies, providing case study examples and ideas for further research'--
Keywords: Language and languages -- Study and teaching -- Research; Discourse analysis, Narrative; Linguistic analysis (Linguistics); Second language acquisition -- Research; Applied linguistics